A Functional Review of Research on Clarity, Immediacy, and Credibility of Teachers and Their Impacts on Motivation and Engagement of Students - Zheng, Jin (Frontiers in Psychology, 2021)
Teachers’ interpersonal communication behaviors have been substantiated to affect students’ motivation, engagement, and success in academic arena. Aiming to provide a systematic review of some teacher-related constructs in this domain, the present article was a bid to explain the crucial pillars of teacher’s clarity, credibility, and immediacy in juxtaposition with theories and models of student’s motivation and engagement. More particularly, this article presents some theoretical underpinnings to justify its claims using the ideas of positive psychology, the broaden-and-build theory, the rhetorical/relational goal theory, social cognitive theory, the attachment theory, some popular motivational theories, and the engagement theory. These theories signify the importance of teacher’s clarity, credibility, and immediacy in the classroom and clearly depict their association and impact on students’ motivation and engagement. Next, the arguments are defended through a quick glance at the available empirical studies on each of the constructs. Then, the findings and implications of this review article are discussed. Finally, research gaps and future directions are presented for avid researchers to make new explorations.